De la nécessité des recherches méta-glottodidactiques au sein de la communauté polonaise des spécialistes dans l’enseignement/apprentissage des langues étrangères - Orchowska, Izabela (Glottodidactica, 2015)
The present paper is based on the assumption that the current state of the development of the FL didactics in its epistemological and discursive dimensions justifies the need for metaglottodidactic research. This kind of research could facilitate the consolidation of glottodidactic subdomains and the knowledge created within these subdomains and contribute to elucidating some epistemological and discursive problems important for the functioning of the Polish glottodidactic community. Further, this could optimize the dialogue within the glottodidactic community, as well as the interdisciplinary dialogue with the representatives of the allied sciences.